Acting 'As If’: Symbolic Politics and Social Control in Syria - Wedeen, Lisa (جماعة, 2003)
In this article, Wedeen examines how under the Syrian president Hafez al-Assad a personality cult has become an effective means at maintaining power. She argues that this personality cult fosters a political culture based on obedience in requiring citizens to actively participate in it. Of less concern to the Ba'athist regime is legitimizing its rule or expecting the public to believe in this cult. Rather, the regime accrues power by effectively making citizens “act as if” they are willful parties to the personality cult. At the same time, citizens can and do use the very symbols promoted in the cult to undermine the regime.